Tunable near white light photoluminescence of lanthanide ion (Dy3+, Eu3+ and Tb3+) doped DNA lattices - Dugasani, Sreekantha Reddy; Park, Byeongho; Gnapareddy, Bramaramba; Pamanji, Sreedhara Reddy; Yoo, Sanghyun; Lee, Keun Woo; Lee, Seok; Jun, Seong Chan; Kim, Jae Hun; Kim, Chulki; Park, Sung Ha (ROYAL SOC CHEMISTRY, 2015)
For more than two decades, structural DNA nanotechnology has been investigated, yet researchers still have not clearly determined the functional changes and the applicability of DNA structures resulting from the introduction of a variety of ions. Lanthanide ions, such as Dy3+, Eu3+ and Tb3+, are interesting rare earth ions that have unique characteristics applicable to photonics. Here, we have constructed lanthanide ion doped double-crossover DNA lattices, a new class of functional DNA lattices, grown on a silica substrate. Deformation-free lattices were fabricated on a given substrate, and dopant ions were introduced to study their photoluminescence characteristics. The photoluminescence of the lanthanide ion-doped DNA lattices exhibited broad emission spectra in the visible region and a tendency of near white light emission composed of various colours. The intensity of the distinct spectral lines produced by the photoluminescence increased as the doping concentration of the ions reached the critical point, and the intensity then decreased with a further increase in the ions. Photoluminescence quenching was also observed when the excitation wavelength increased. These phenomena are the result of energy transfer between the DNA and the dopant ions. Finally, we make use of chromaticity diagrams to identify the colour coordinates of the luminescence produced by the lanthanide ion-doped DNA lattices, and this information may be useful to construct efficient bio-photonic devices or sensors in the future.
Keywords: THIN-FILM; MOLECULES; NANOSTRUCTURES; INTERCALATION; PRINCIPLES; CRYSTALS; COMPLEX